Comparison of efficacy between palonosetron-midazolam combination and palonosetron alone for prevention of postoperative nausea and vomiting in patients undergoing breast surgery and patient controlled analgesia: A prospective, randomized, double-blind study. Issue 26 (2nd July 2021) - Hong, Jeong-Min; Han, Yun-Hee; Lee, Dowon; Hwang, Boo Young; Baik, Jiseok; Cho, Ah Reum; Lee, Hyeon Jeong; Kim, Eunsoo
Abstract: Background: Postoperative nausea and vomiting (PONV) is a common complaint in patients following general anesthesia. Various antiemetics, including 5-hydroxytryptamine type 3 (5-HT3 ) receptor antagonists, are effective but still have limited efficacy. Therefore, combination therapy is preferable to using a single drug alone in high-risk patients. We performed a comparative study on the antiemetic effect of palonosetron, a 5-HT3 receptor antagonist, monotherapy vs palonosetron-midazolam combination therapy for the prevention of PONV. Methods: A total of 104 female patients scheduled for breast cancer surgery were enrolled. They were randomly divided into 2 groups, a palonosetron monotherapy group (group P) and palonosetron-midazolam combination therapy group (group PM). Both groups received 0.075 mg palonosetron intravenously after induction of anesthesia. Patient-controlled analgesia (PCA) was applied according to the allocated group. Intravenous (IV)-PCA in group P consisted of fentanyl 20 μg/kg plus normal saline (total volume: 100 ml); IV-PCA in group PM consisted of fentanyl 20 μg/kg plus midazolam 4 mg plus normal saline (total volume: 100 ml). Efficacy parameters were collected during 0 to 1, 1 to 6, 6 to 24, and 24 to 48 hours postoperative time intervals. These measures included complete response (defined as no PONV and no rescue anti-emetic use) rate, incidence of PONV, sedation score, rescue antiemetic use, rescue analgesic use, and numerical rating scale (NRS) for pain. The complete response rate during the 0 to 24 hours interval was analyzed as the primary outcome. Results: Although the complete response rate between 0 and 24 hours was higher in group PM (42.3% and 48.1% in group P and PM, respectively), there was no statistically significant difference ( P  = .55). The complete response rates in other time intervals were not different between the 2 groups as well. The sedation score and NRS score also showed no differences between the 2 groups. Conclusions: The combination therapy of palonosetron with midazolam did not lead to a greater reduction in the incidence of PONV than monotherapy in patients undergoing breast surgery and receiving IV-PCA containing fentanyl.